Effects of different inclusion of sirulina meal on growth, survival and feed utilization of juvenile Asian seabass (Lates calcarifer) reared in freshwater - Tan, Chin Yong (2015)
The objective of this study is to evaluate the possibility of Spirulina meal (SP) to replace fish meal in the diet of Asian seabass, Lates calcarifer. Five isoproteic (45% crude protein) and isolipid (12% crude lipid) diets were formulated to replace FM with 0 (control), 5, 10, 20 and 30% Spirulina (as SP0, SP5, SP10, SP20 and SP30 respectively) and fed to fish (initial body weight, 6.00±0.02g) for eight weeks. Triplicate group of 20 tails juvenile Asian seabass were stocked in recirculating aquaculture system. At the end of feeding trial, there was no Significance difference (p>0.05) in term of weight gain, specific growth rate, feed intake, protein efficiency ratio, feed conversion ratio, viscerosomatic index and condition factor. Fish fed SP0 showed significantly higher (p<0.05) survival compared to SP20 and SP30 but no significance difference from fish fed SP5 and SPI0. The weight gain of juvenile Asian seabass ranged from 109.03% to 198.35% whereby SP10 showed the highest compared to SP0 and SP30 was the lowest. The highest feed intake was from fish fed SP10 and was statistically proven (p<0.05). There was significance difference in hepatosomatic index (HSI) whereby HSI increased with higher inclusion level of SP ranged from 0.81 to 1.51. Whole body-proximate composition were significantly affected by the inclusion of SP in diet of Asian seabass. The present study indicate replacement level 5-10% inclusion are recommend for a long term use.